2016
DOI: 10.1111/sji.12455
|View full text |Cite
|
Sign up to set email alerts
|

Siglec‐7 Defines a Highly Functional Natural Killer Cell Subset and Inhibits Cell‐Mediated Activities

Abstract: Sialic acid-binding immunoglobulin-like lectin-7 (Siglec-7) is an inhibitory receptor expressed on natural killer (NK) cells. In this study, we investigated the relationship between Siglec-7 expression and NK cell functions. Siglec-7 was highly expressed on NK cells and was preferentially expressed by mature NK cells from peripheral blood of healthy adults. Siglec-7 + NK cells displayed higher levels of activating receptors CD38, CD16, DNAM1, NKp30 and NKp46, but lower levels of inhibitory receptors such as NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 55 publications
3
53
0
Order By: Relevance
“…FAS (CD95), which plays a central role in the physiologic regulation of programmed cell death and is up‐regulated on NK cells in response to cytokines, was down‐regulated at W8 on total and effector NKs. Siglec‐7, an NK cell inhibitory receptor, was up‐regulated on these populations at the same time (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FAS (CD95), which plays a central role in the physiologic regulation of programmed cell death and is up‐regulated on NK cells in response to cytokines, was down‐regulated at W8 on total and effector NKs. Siglec‐7, an NK cell inhibitory receptor, was up‐regulated on these populations at the same time (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes in NK phenotype that we observed late (predominantly 12 weeks after the end of treatment), comprising decreased expression of activation (CD69, CD161) and cytotoxicity (NKp30, NKp46, and TRAIL) receptors, suggest that the chronically activated NK phenotype characteristic of chronic HCV is reversed by ledipasvir/sofosbuvir therapy but that normalization of the activation status takes several weeks after the disappearance of virus. The expression patterns of FAS (CD95) and Siglec‐7 (CD328), which are altered at intermediate time points (W4‐W12), suggest that down‐regulation of the activation status of NK cells is a gradual process …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siglec-7 is a sialic acid-binding protein that has an immune tyrosine-based inhibition motif (ITIM). Siglec-7 is expressed on highly active NK cells (56), and loss of expression is believed to correspond to dysfunction of NK cells, which occurs in chronic HIV and HCV infection (46,57). CD11b is a marker of maturation of NK cells in humans and mice (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Although Siglec-7 is an iNKRs containing ITIM-like domains in its cytosolic tail, it has been also reported that Siglec-7 pos NK cells are more functionally relevant compared to their Siglec-7 neg counterparts. Indeed, the expression of Siglec-7 in NK cells is associated with higher levels of aNKRs (i.e., CD16, NKp30, NKp46) and lower levels of iNKRs (i.e., CD94/NKG2A, CD158b) (76). This likely explains the fact that NK cells still retain a certain degree of antiviral and antitumor functions in the acute phases of HIV-1 infection, while become anergic and highly dysfunctional only in the chronic stages of the disease featuring the expansion of the Siglec-7 neg /CD56 neg NK cells (56).…”
Section: Kinetics Of Siglecs During the Course Of Hiv-1 Infectionmentioning
confidence: 99%